2021
DOI: 10.1186/s12887-021-02844-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the availability of medical oxygen and its clinical practice in Ethiopia during a national scale-up program: a time series design from thirty-two public hospitals

Abstract: Background Oxygen therapy is a lifesaving treatment, however, in Ethiopia, oxygen is not readily available in many healthcare facilities. In 2015, the Federal Ministry of Health launched a national roadmap to increase access to oxygen. This study aims to evaluate whether availability of oxygen and its clinical practice in public hospitals of Ethiopia changed during the time the roadmap was being implemented. Methods Between December 2015 and Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…One component of this five-year strategy was pressing for a new policy on oxygen and pulse oximetry scale-up. The results from this wide-scale approach lead to functional oxygen availability from 62 to 100% in pediatric wards, and increasing the availability of pulse oximetry from 45 to 96% [ 39 ]. Adoption of pulse oximetry in Nigerian centers indicated swift implementation, with reporting on > 90% of admitted children within 6 to 12 months of commencement [ 40 ].…”
Section: Solutionsmentioning
confidence: 99%
“…One component of this five-year strategy was pressing for a new policy on oxygen and pulse oximetry scale-up. The results from this wide-scale approach lead to functional oxygen availability from 62 to 100% in pediatric wards, and increasing the availability of pulse oximetry from 45 to 96% [ 39 ]. Adoption of pulse oximetry in Nigerian centers indicated swift implementation, with reporting on > 90% of admitted children within 6 to 12 months of commencement [ 40 ].…”
Section: Solutionsmentioning
confidence: 99%
“…Oxygen therapy is used to treat many diseases which present with hypoxemia, a serious condition caused by low levels of oxygen in the blood [2]. Pneumonia is the largest infectious cause of death in children worldwide, claiming the lives of an estimated 800,000 children under the age of five, which is equivalent to around 2200 children every day [3]. Supplemental oxygen is among the most administered medical therapies in hospitalized patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…In many hospitals, supplemental oxygen can be administered and titrated without a physician order, in contrast to most medications [5]. New hypoxemia is a cardinal bedside sign of acute or impending decompensation as well as a marker of disease severity for several chronic comorbidities [3]. Oxygen is a commonly used drug in the clinical setting and like other drugs its use must be considered carefully [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 32 national hospitals indicated that during this time, the functional availability of pulse oximetry increased from 45%-86%. 21 In addition, the Ethiopian government implemented the Acute Respiratory Infection Diagnostic Aids (ARIDA) initiative supported by United Nations Children’s Emergency Fund (UNICEF). The aim of the ARIDA initiative was to identify and test innovative diagnostic tools to improve the identification, classification and management of children with pneumonia.…”
Section: Introductionmentioning
confidence: 99%